2003
DOI: 10.1177/154405910308201204
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Intrafibrillar Mineralization of Collagen on the Mechanical Properties of Dentin

Abstract: It is widely held that the hardness and modulus of dentin increase in proportion to the mineral concentration. To test this belief, we measured hardness and modulus of normal dentin and an altered form of dentin without gap-zone mineralization in wet and dry conditions by AFM nanoindentation to determine if the modulus and hardness scale linearly with mineral concentration. Mineral concentrations in the mid-coronal location of the normal and altered dentins were 44.4 vol% and 30.9 vol%, respectively. Surroundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
217
1
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(234 citation statements)
references
References 19 publications
9
217
1
7
Order By: Relevance
“…Another possible explanation is that dentin collagen is reinforced by intrafibrillar mineral and each fibril is surrounded by extrafibrillar mineral. The intrafibrillar mineral, which stiffens the collagen fibrils, dominates the elastic behavior under normal loading conditions [25].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation is that dentin collagen is reinforced by intrafibrillar mineral and each fibril is surrounded by extrafibrillar mineral. The intrafibrillar mineral, which stiffens the collagen fibrils, dominates the elastic behavior under normal loading conditions [25].…”
Section: Discussionmentioning
confidence: 99%
“…The Young's modulus of coronal intertubular dentin was 26.60±2. 19 GPa, while that of radicular dentin was 20.89±1.10 GPa. Results showed that the hardness and Young's modulus of coronal intertubular dentin were greater than those ofradicularintertubulardentin.…”
Section: Hardness and Young's Modulus Measurements Of Coronal And Radmentioning
confidence: 99%
“…Hence, the aim of this study wastodetermineandcomparethenanohardnessand Young's modulus of coronal and radicular intertubular dentin. Indentation is widely used to evaluate hardness and Young's modulus for dentin 1,[15][16][17][18][19][20][21][22][23] .Thisisbecausenanoindentationresults inverysmallindentedregions,makingitpossibleto clarifytheintertubulardentinpropertiesirrespective ofperitubulardentinorthedentinaltubules.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these tested materials have the ability of delivering calcium and phosphate ions to promote regrowth of remnant apatite crystals within the intrafibrillar zone of collagen fibrils (via classic nucleation) [6]. A second route to remineralization exists based upon biomineralization mediated by amorphous calcium and phosphate precursors (ACP) and polyanionic polymers [7].…”
Section: Introductionmentioning
confidence: 99%